2022
DOI: 10.14245/ns.2143196.598
|View full text |Cite
|
Sign up to set email alerts
|

Hemostats in Spine Surgery: Literature Review and Expert Panel Recommendations

Abstract: Bleeding in spine surgery is a common occurrence but when bleeding is uncontrolled the consequences can be severe due to the potential for spinal cord compression and damage to the central nervous system. There are many factors that influence bleeding during spine surgery including patient factors and those related to the type of surgery and the surgical approach to bleeding. There are a range of methods that can be employed to both reduce the risk of bleeding and achieve hemostasis, one of which is the adjunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 82 publications
(107 reference statements)
0
8
0
Order By: Relevance
“…More excessive bleeding may negatively affect the visualization during endoscopic spinal procedures. Similar to other surgeries, several options are available for us to use for achieving better hemostasis control during endoscopic spinal surgery, including radiofrequency ablation probes or various types of hemostatic agents, such as bone wax, gelatin foam, or human gelatine-thrombin matrix sealant [ 40 ]. The manual control pressure of the saline irrigation for a brief period is also an advantage in full-endoscopic spine surgery.…”
Section: Discussionmentioning
confidence: 99%
“…More excessive bleeding may negatively affect the visualization during endoscopic spinal procedures. Similar to other surgeries, several options are available for us to use for achieving better hemostasis control during endoscopic spinal surgery, including radiofrequency ablation probes or various types of hemostatic agents, such as bone wax, gelatin foam, or human gelatine-thrombin matrix sealant [ 40 ]. The manual control pressure of the saline irrigation for a brief period is also an advantage in full-endoscopic spine surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The goal for treatment of unstable atlas fractures is to reduce fracture displacement, maintain stabilization, and heal the bony fracture. Various surgical options for treating unstable atlas fractures with ligament tears have been recently described with advanced surgical techniques and good radiological outcomes [ 7 - 9 , 13 , 17 - 20 ]. However, in these times of favorable results by surgery, it still remains debatable whether surgery or conservative management should be used for unstable atlas fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Hemostasis is the first crucial step in each neurosurgical procedure, which is almost mandatory to keep a clean operative field in situ and effectively decrease potential blood loss and post‐operative complication. [ 160 ] Although the medico‐economic data in one French hospital showed that neurosurgery (including spine surgery) was the greatest consumer of surgical hemostats and had a great deal of expenditure for advanced hemostatic techniques, [ 161 ] local hemostatic materials were quite limited to be used for surgical and traumatic bleedings in cranial cavity or spinal cord. Previous studies evidenced that RADA16 peptide hydrogel promoted nerve fiber growth and enhanced the functional recovery of acute brain injury in the behavioral detection system of intracerebral hemorrhage (ICH).…”
Section: Clinical or Preclinical Use Of Dsap Biomaterials In Surgical...mentioning
confidence: 99%